The BFG - Dahl, Roald; Blake, Quentin (New York, New York : Puffin Books, 2016)
The Big Friendly Giant is no ordinary bone-crunching giant. He is far too nice and it's lucky for Sophie that he is. If she had been carried off by any of the other giants she would have been breakfast. When Sophie hears that the giants are headed to England to steal some little children, she and the BFG decide they must stop them once and for all.
"Now a major motion picture" - Cover.
Keywords: Giants -- Juvenile fiction; Orphans -- Juvenile fiction